A quantitative validation of a qualitative phenomenological art-therapy cross-cultural study - Wyder, Silvia (Frontiers in Psychology, 2025)
IntroductionThis art therapy and cross-cultural research (France, Switzerland and Japan) investigated the topical suggestion of the ‘house’ in psychiatric settings via painting and drawing. The aim was to search whether this theme could serve as a symbolic representation of patients’ selfhood, and if it would allow pictorial, and, or verbal manifestation of Posttraumatic Stress Disorder phenomena. This paper focuses on presenting the developed mixed-methods study strategy and the obtained results.MethodsA qualitative phenomenological approach was applied in order to gain in-depth pictorial and narrative patient-based material through retroactive note taking from memory. Further data sets consisted of semi-structured interviews and closing discussions. A focus groups art therapy method was carried out focusing on individuals’ behavior, and group dynamics. A phenomenological coding procedure was applied following, allowing searching for emerging themes and patterns. A quantitative analysis was carried out by examining the phenomenological qualitative material, including semi-structured interview data. The study included 30 adult (out-patients) and adolescent (closed unit) patients (15-68 years).ResultsBased on the carried out coding procedure seven overarching clusters could be identified such as ‘House/Home’, ‘Human Relationship’, ‘Inner Life’,‘Physical/Mental Health’, ‘Culture’, ‘Nature’, and ‘Aesthetic’. These clusters permitted highlighting similarities and distinctions between three socio-culturally and age-related diverse groups irrespective of the clinical setting. Matching cluster occurrence rates were observed in all three data sets in all three venues.DiscussionThe findings attest a pronounced topical self-reference via ‘house’ paintings and drawings. Methodologically, the results demonstrate the validity of the carried out phenomenological qualitative research strategy in quantitative terms; this mixed-methods approach is thus an effective procedure in art therapy research. The result is particularly salient within the longest five months’ fieldwork study (Switzerland).